Threats and conservation status of threatened birds in Chitwan Annapurna Landscape, Nepal (Nepal Journal of Environmental Science, 2025)
Chitwan-Annapurna Landscape (ChAL), a biologically diverse region in Nepal, is progressively being influenced by human activities. This has impacted population and habitat of nationally and internationally threatened bird species. To identify ongoing threats for these birds, we conducted field surveys and expert opinions. Field surveys were performed using a grid-based point-count method (within a 50-meter radius), throughout 472 accessible 1 km² grids during the winter (November–February) and summer (April–July) seasons of 2020 and 2021. Species were classified using the IUCN Red List and the National Red List of Nepal, and threats were documented using the IUCN threat categorization scheme. Scope, severity and urgency were ranked qualitatively. Among the identified birds, globally, nine species were categorized as Near Threatened (NT), four as Vulnerable (VU), three as Endangered (EN), and three as Critically Endangered (CR). Pollution was the most prominent threat, followed by alterations to natural systems, residential and commercial building, and transportation infrastructure. Several threats were found to significantly affect species such as the Grey-crowned Prinia (Prinia cinereocapilla), Common Pochard (Aythya ferina), and Red-breasted Parakeet (Psittacula alexandri). These results highlight the significance of ChAL for bird conservation and the need of adopting immediate measures to reduce pollution, manage regional risks, and regulate habitat modification. For bird diversity to survive in this ecologically critical area over the long run, species-specific conservation techniques are advised in addition to routine monitoring and updated threat assessments. Safeguarding the ChAL from pollution, habitat degradation and human pressure is essential to conserve its threatened bird species and maintain long term ecological balance.